2014
DOI: 10.1159/000365026
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Obesity, Interventions, and Mechanistic Pathways to Impaired Health in Offspring

Abstract: Background: The global rates of male overweight/obesity are rising, approaching 70% of the total adult population in Western nations. Overweight/obesity increases the risk of chronic diseases; however, there is increasing awareness that male obesity negatively impacts fertility, subsequent pregnancy, and the offspring health burden. Developmental programming is well defined in mothers; however, it is becoming increasingly evident that developmental programming can be paternally initiated and mediated through p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 30 publications
1
62
1
4
Order By: Relevance
“…Because father-to-embryo transmission excludes gestational effects, mechanistically, imprinting, altered DNA methylation, histone modifications, and noncoding RNA changes in sperm or alterations to seminal plasma composition, which can influence the signaling of the female reproductive tract, have been implicated in paternal nongenetic transmission (9,53). In Drosophila, consumption of a high-sugar diet by fathers alters the chromatin state of metabolic dependent genes in offspring, which persisted into embryos and which were originally altered in sperm (68).…”
Section: Alterations To Fetal Health From Combined Paternal and Matermentioning
confidence: 99%
“…Because father-to-embryo transmission excludes gestational effects, mechanistically, imprinting, altered DNA methylation, histone modifications, and noncoding RNA changes in sperm or alterations to seminal plasma composition, which can influence the signaling of the female reproductive tract, have been implicated in paternal nongenetic transmission (9,53). In Drosophila, consumption of a high-sugar diet by fathers alters the chromatin state of metabolic dependent genes in offspring, which persisted into embryos and which were originally altered in sperm (68).…”
Section: Alterations To Fetal Health From Combined Paternal and Matermentioning
confidence: 99%
“…Several studies showed that also paternal nutritional factors, in particular during maturation of the sperm, may alter the epigenome and the phenotype of the offspring [27-30]. …”
Section: Introductionmentioning
confidence: 99%
“…In animal studies, Sertoli cell development and, potentially, sperm production, are affected by maternal nutrition during pregnancy (Olsen et al, 2000;Genovese et al 2010). Paternal lifestyle, behavior and environmental exposure may impact offspring as well (McPherson et al, 2014;Soubry et al, 2014). However, evidence from epidemiologic studies of peri-conceptional effects on offspring reproductive function is limited and equivocal (Power et al, 2003;Dupont et al, 2012).…”
Section: Introductionmentioning
confidence: 99%